Identification of Sources of Variation in Poverty Outcomes - Essama-Nssah, B. (2012)
The international community has declared poverty reduction one of the fundamental objectives of development, and therefore a metric for assessing the effectiveness of development interventions. This creates the need for a sound understanding of the fundamental factors that account for observed variations in poverty outcomes either over time or across space. Consistent with the view that such an understanding entails deeper micro empirical work on growth and distributional change, this paper reviews existing decomposition methods that can be used to identify sources of variation in poverty. The maintained hypothesis is that the living standard of an individual is a pay-off from her participation in the life of society. In that sense, individual outcomes depend on endowments, behavior and the circumstances that determine the returns to those endowments in any social transaction. To identify the contribution of each of these factors to changes in poverty, the statistical and structural methods reviewed in this paper all rely on the notion of ceteris paribus variation. This entails the comparison of an observed outcome distribution to a counterfactual obtained by changing one factor at a time while holding all the other factors constant.